(untitled) (Research, Society and Development, 2021)
Phrynops geoffroanus is a testudine of the family Chelidae that has a wide distribution. However, there are gaps in the knowledge of its biology. This study aimed to characterize demographically and morphometrically a population of Phrynops geoffroanus in an ephemeral water reservoir in a semi-arid area of Paraíba, in the period from April 2016 to March 2017. The individuals were captured manually and by hoop-net trap. Data on size distribution were described by mean and standard deviation. Size and weight were compared between sexes and capture methods using a MANOVA. Sex ratio was compared between capture methods using Pearson’s chi-squared test. Population density and biomass were calculated. The number of animals captured was grouped into two shifts and compared. Throughout the year, 113 individuals of P. geoffroanus were captured in the reservoir, with a population of 43.4% males, 47.8% females and 8.8% juveniles, with a density of at least 41.8 individuals / ha and biomass of 33.05kg / ha. There is no significant relationship between the amount of animals captured and the amount of rainfall during the period sampled. Due mainly to the ephemerality of the aquatic environments of the Caatinga and the unpredictability of rainfall in this biome, the populations of aquatic species show large variations in population and in their biological activities. Further studies are needed to fill several gaps in the knowledge of the natural history of Caatinga testudines.